Through the Teacher's Lens: Perspectives on Integrating Higher-Order Thinking Skills into Mathematics Instruction - Gradini, Ega; Noviani, Julia; Samsudin, Syafiza Saila (Universitas Muhammadiyah Mataram, 2025)
The integration of Higher-Order Thinking Skills (HOTS) in mathematics instruction holds significant potential to deepen students’ conceptual understanding and fostering analytical thinking. However, its implementation is often hindered by gaps in teacher competency, curricular limitations, and outdated assessment methodologies. This study aims to explore mathematics teachers’ perspective on HOTS integration by examining four dimensions: understanding, perceived need, implementation challenges, and classroom practices. A descriptive survey design was employed, involving 186 junior and senior high school teachers selected through stratified random sampling. Data were collected via a structured questionnaire and analyzed using descriptive and inferential statistics, including Pearson correlation. Findings reveals a noticeable gap between teachers’ conceptual understanding of HOTS and its practical application in the classroom. While teachers acknowledge the importance of HOTS and frequently incorporate problem-solving and analytical activities, practical application is inconsistent due to time constraints, insufficient training, and limitation of resources. Differences were observed across teaching levels and school types: private and senior high school teachers, showing stronger understanding and more frequent HOTS integration. Weak correlation among understanding, perceived need, and practice indicate that awareness alone does not ensure effective implementation. These findings underscore the need for systematic support, targeted professional development, and policy reforms to bridge the gap between theory and practice. The study contributes to educational practice by highlighting actionable areas for institutional support and inform policy development aimed at enhancing the integration of HOTS in mathematics education.